RISK MITIGATION IN THE FOOD CORN SUPPLY CHAIN: A CASE STUDY IN KEDIRI REGENCY - Andika Yuli Heryanto; Rahmat Tata Pratama; Hadi Prastyo (Universitas Sebelas Maret, 2025)
Kediri Regency is one of the corn production centers in East Java. UD. XYZ is an MSME from Kediri Regency that produces processed food products from corn, namely marning. Operational activities and supply chain at UD. XYZ causes risk events. This study aims to identify, analyze, evaluate, and mitigate risks at each food corn supply chain tier. The research sample was determined using convenience and snowball sampling. The risks at the farmer level are 15 risks. The risks at the collector trader and MSME levels are seven risks and 11 risks. The vulnerability risk event matrix at the farmer tier shows extremely vulnerable (F 1.10 and F 1.12), highly vulnerable (F 1.4, F 1.5, and F 1.14), and moderate vulnerability (F 1.3, F 1.13, and F 1.15). The vulnerability risk event matrix at the collector trader tier shows low vulnerability at risks CT 2.1, CT 2.2, CT 2.3, CT 2.4, and CT 2.5. The vulnerability risk event matrix at the MSME tier shows highly vulnerable (C 4.1, C 4.2, C 4.10, and C 4.11), moderate vulnerability (C 4.7), and low vulnerability (C 4.6). Risk mitigation is carried out for risk events that are extremely vulnerable, highly vulnerable, moderately vulnerable, and low vulnerability.